Use of remote sensing to identify areas at risk of degradation in the semi-arid region (Revista Ciência Agronômica, 2018)
One of the most effective procedures in the evaluation of degraded areas has been the use of remote sensing.The aim of this work was to evaluate the temporal dynamics of the NDVI and rainfall in detecting the degradation of naturalresources in a semi-arid region of Brazil. The area under study is located to the west of the district of Tauá, in the State of Ceará,with a predominance of shrub-like caatinga forest. Rainfall data was obtained from FUNCEME. Ten images (dry season) wereacquired from a 27-year historical series (1985-2011) from the TM/LANDSAT5 sensor, later converted to surface reflectanceusing the FLAASH/ENVI extension; NDVI indices were obtained and divided into six classes corresponding to land usage andoccupation. The mean values of the NDVI classes were submitted to statistical analysis and compared by T-test (p